Sovereignty, Robustness, and Short-Term Energy Security Levels. The Catalonia Case Study - Rosas-Casals, Martí; Marzo, Mariano; Salas-Prat, Pep (Frontiers in Energy Research, 2014)
Energy related impacts and conflicts have been used to account for the emergence, maintenance and collapse of complex societies. On the other hand in the last years, sustainability science has incorporated different frames of reference in order to facilitate the vision of sustainable futures. Most of them suggest that the search for satisfiers of human needs should be rooted on the local (a) construction of organic articulations of people with nature and technology and (b) generation of growing levels of social, economic and energy self-reliance. This new regional kind of social agreement implies a redefinition of cultural norms and institutions, which at the same time leads toward increased levels of sovereignty for the social group engaged in this process. Sovereignty must not only be understood here in its political sense (as traditionally found in the literature) but also in its technological and energy acceptations. In this paper we address this last constituent in terms of energy security levels and hierarchy in energy infrastructures between Spain and Catalonia, the latter being a Spanish autonomous community known for its sovereignty aspirations. We show a remarkable difference in energy security levels between both regions which clearly hinders Catalonia’s capacity to currently achieve a higher level of self-reliance in energetic terms. We suggest that this result is a consequence of the imperfect hierarchy that characterize energy infrastructures at the spatial scale, and that it can be generalized to all regions where infrastructural systems have been historically assessed and developed under a nationwide planning scheme.